2009
DOI: 10.1093/ndt/gfp071
|View full text |Cite
|
Sign up to set email alerts
|

Residual renal function improves outcome in incremental haemodialysis despite reduced dialysis dose

Abstract: The associations demonstrated suggest that residual renal function contributes significantly to outcome in HD patients and that efforts to preserve it are warranted. Comparative outcome studies should be controlled for residual renal function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
163
2
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 144 publications
(180 citation statements)
references
References 38 publications
12
163
2
3
Order By: Relevance
“…A relation between decline of RRF and more severe anemia and increased ESA resistance has been recognized previously in PD patients (1,10), but data in HD patients have been limited. Recently, it was shown that the mean ESA resistance index over time was 10% to 30% lower in patients with residual urea clearance Ն1 ml/min as compared with patients with residual urea clearance Ͻ1 ml/min (15). In the latter study, C-reactive protein levels were not statistically different between the low and high RRF groups.…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…A relation between decline of RRF and more severe anemia and increased ESA resistance has been recognized previously in PD patients (1,10), but data in HD patients have been limited. Recently, it was shown that the mean ESA resistance index over time was 10% to 30% lower in patients with residual urea clearance Ն1 ml/min as compared with patients with residual urea clearance Ͻ1 ml/min (15). In the latter study, C-reactive protein levels were not statistically different between the low and high RRF groups.…”
Section: Discussionmentioning
confidence: 74%
“…This may translate to better volume control, less necessity for stringent fluid and salt restriction, and generally fewer intradialytic symptoms in patients with RRF. In view of the potential important role of RRF on multiple biochemical and clinical outcomes, controlling for RRF in observational studies should be considered (15), even if the GFR is very low.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…19 RRF not only improves the nutritional status and quality of life, but also reduces the mortality in patients with chronic dialysis. 20 RRF is evaluated by the mean of creatinine and urea clearance rate and corrected with the body surface area. Detection of creatinine and urea clearance is a heavy burden for chronic dialysis patients because it requires collection of urine for 24 h. Therefore, some studies used the dialysis between 24 h urine to evaluate RRF.…”
Section: Discussionmentioning
confidence: 99%